Analisis Pengaruh Faktor-Faktor Positioning Produk Terhadap Citra Merek Pada Produk Roudup Biosorb 480 SL di Brebes Selatan - Mukhroji Mukhroji (Universitas Peradaban, 2017)
The purpose of this study was to determine the effect on the brand image of products positioning (study cases of Roundup Biosorb 480 SL). This study used 58 respondents from the village in six subdistricts (Tonjong subdistrict, Bumiayu subdistrict, Sirampog subdistrict, Paguyangan subdistrict, Bantarkawung subdistrict, Salem subdistrict), each 1 respondent representing a village. The sampling method uses purposive techniques or probability sampling, which is the selection of a random sample obtained by certain considerations. The data testing used in this study is to test the data outliers, processed by the classical assumption. This research uses a statistical method possible canonical correlation analysis. The result of the study showed that there is a significant relationship between positioning, value, usage, class, competitors, and benefit, with brand image, through excellence, strength, and uniqueness. It can be seen from the test results as of significant multivariate under the level of confidence.